Peningkatan Keterampilan Masyarakat Desa untuk Membuat Jamu Nusantara Tersaintifikasi sebagai Produk Unggulan Desa - Nugroho, Wahyu; Ayuchecaria, Noverda; Riani, Defilia Anogra; Citrariana, Shesanthi; Gintoro, Atilla Dian Dewanti; Krissilvio, Eka Jonathan (Borneo Research and Education Center, 2024)
Herbal medicine is a hereditary heritage of local wisdom of the Indonesian people. The Ministry of Health through the Health Research and Development Agency runs a herbal medicine scientification program. However, there are still few people who understand how to make scientific herbal medicine. The purpose of this community service is to disseminate the skills of making scientific herbal medicine concoctions to the community. Community service was carried out in Tuwung Village, Kahayan Tengah District, Pulang Pisau Regency, Central Kalimantan Province with the method of providing material and training in making scientific herbal medicine directly. Participants were given a questionnaire to start the satisfaction of the community service services carried out including Reliability, Responsiveness, Assurance, Empathy, Tangible evidence. The results of the community service showed that all dimensions scored Good.